Career aspirations and trajectories of geographies of health and health care graduates: A cross‐sectional study. (23rd January 2022) - Barakat, Caroline; Crighton, Eric; Cardwell, Francesca; Yousufzai, Susan
Abstract : Despite the diverse academic training of health geographers and their capacity to think spatially and temporally when focusing on complexities of people's health in changing environments, career‐related concerns have been raised due to the dearth of academic jobs in the sub‐discipline. Given these concerns, an understanding of the career aspirations and trajectories of health geography graduates, as well as their experiences within and outside academia, has the potential to inform the progression and evolution of the sub‐discipline. This cross‐sectional study of members of the Geography of Health and Health Care Specialty Group of the Canadian Association of Geographers (n  =  56) found that acquiring academic work remains the desired career goal for many geography graduates. While a majority of participants aspired to work in academia, some participants reported insecurity in obtaining academic jobs, and precarity in this trajectory. Although belonging to the specialty group has contributed positively to the experiences of graduates in providing network opportunities and job positions, there were calls for critical engagement of the group in mentorship, networking, and increasing exposure to careers outside of academia to help inform the future direction and the inter‐relationship of academics within the sub‐discipline of health geography . Key Messages: Tracking the career trajectories of health geographers improves our understanding of the roles they pursue as they contribute to knowledge and policy in Canada and globally. Although most health geography graduates aspire to pursue career paths in academia, there is scarcity in academic work, creating a need for guidance on alternative career paths. To improve our understanding of the career trajectories of health geographers, future research may benefit from collaborating with geography departments with a focus in health geography to track Canadian graduates. Aspirations professionnelles et trajectoires des diplômés en géographie de la santé et des soins de santé: une étude transversale: Malgré la formation universitaire diversifiée des géographes de la santé et leur capacité à réfléchir spatialement et temporellement lorsqu'ils se concentrent sur la complexité de la santé des populations dans des environnements changeants, on remarque des inquiétudes chez ceux‐ci en raison de la pénurie d'emplois dans ce domaine en milieu universitaire. Dans ce contexte, une meilleure compréhension de leurs aspirations professionnelles et des trajectoires des diplômés, de même que de leurs expériences tant à l'intérieur qu'à l'extérieur du milieu universitaire, nous permet de documenter la progression et l'évolution de la sous‐discipline. Cette étude transversale réalisée par certains membres du Groupe spécialisé en géographie de la santé et des soins de santé de l'Association canadienne des géographes (n = 56) fait ressortir que l'obtention d'un emploi en enseignement et recherche universitaires demeure l'objectif professionnel favorisé de nombreux diplômés. Bien qu'une majorité de participants aspirent à travailler en milieu universitaire, certains participants ont exprimé de l'insécurité face à la précarité de cette trajectoire. Par ailleurs, si l'appartenance au groupe spécialisé a contribué positivement aux expériences des diplômés, il y a eu de fortes demandes de participation du groupe au mentorat, au réseautage et à la promotion des carrières possibles à l'extérieur de l'université, afin de mieux informer et encadrer les futurs étudiants .